The Optimal Level of Foreign Reserves in Macedonia - Biljana Jovanovikj; Danica Unevska Andonova (National Bank of the Republic of Macedonia, 2017)
During the last two decades the emerging countries have experienced an upward trend in reserve accumulation. However, high level of foreign reserve assets implies certain costs. Consequently, given the trade-off between the benefits and the costs of holding reserves, there are issues related to the adequacy of the current level of reserves. In this analysis we make an effort to assess the optimal level of the official foreign reserves in Macedonia. The estimation of the optimal level of foreign reserves is based on cost-benefit welfare model as in Jeanne and Ranciere (2011), in which reserves serve as an insurance for the economy and have two roles - to mitigate the negative effects of a capital account crisis (sudden stop) and to prevent future crisis. The model that captures the benefit of holding reserves as self-insurance assumes an exogenous probability of crisis. This basic model shows that the actual level of official reserve assets is above the level for crisis mitigation. In case when reserves are held not only for crisis mitigation purposes, but also for crisis prevention, the probability of crisis is endogenous and depends on the level of reserves. This extended model, which is more suitable for Macedonia regarding the exchange rate regime, shows optimal level of reserves that is still below, but close to the official foreign reserves in recent years.
Keywords: F31; F32; F41; 330; optimal reserves; sudden stop crisis; Macedonia; endogenous probability of crisis